Professional courage for excellence among educational counselors (Journal of the College of Basic Education, 2024)
The relationship between guidance and education is a complementary relationship in our present world and that the guidance process is an important part of modern education as it is based on attention to trends, abilities and skills at various levels and this leads to the individual’s psychological and social adaptation. Guidance is based on two basic pillars: the guide and the mentor. The mentor, by virtue of his training and experience, helps the mentor, as he has the experience, qualifications, and training that help him express his opinion and help the mentor in obtaining scientific and health information in order to reach a strong and compatible self, abandoning the crooked paths, and making the mentor feel responsible for the situations that he takes. It issues from it, and the function of guidance is to prepare people who possess sound and normal selves capable of bearing responsibility and fulfilling professional courage and various life situations. To achieve the objectives of the current research, the researcher adopted a professional courage scale consisting of 3 domains for each domain (10) items, where the scale is as follows: The final score consists of (30) items based on Bury and Saylors’ theory of explaining the concept and constructing the scale. The two scales were then applied to the statistical analysis sample, which amounted to (400) male and female counselors randomly selected from the research community. After correcting the questionnaires for both scales, the researcher extracted the psychometric properties of the courage scale. Professionalism represented by honesty, which includes face validity, item validity, construct validity, and reliability according to the two retest methods, Cronbach’s alpha equation) and extracting the standard error of reliability, as well as other statistical indicators to verify the normality of distribution according to the classical measurement theory followed in construction procedures and performance application, the current research. The researcher applied the two standards to the sample that was selected by cluster randomization in the final form, which amounted to (200) male and female mentors, and after using appropriate statistical methods, the results appeared as follows: . The research sample had professional courage at a level based on the difference between the averag.